3-Mercaptopropyltrimethoxysilane Modified Diatomite: Preparation and Application for Voltammetric Determination of Lead (II) and Cadmium (II) - Dinh Quang Khieu; Bui Hai Dang Son; Vo Thi Thanh Chau; Pham Dinh Du; Nguyen Hai Phong; Nguyen Thi Diem Chau (Journal of Chemistry)
In this study, functionalized diatomite was prepared by grafting of 3-mercaptopropyltrimethoxysilane (MPTMS) to diatomite (MPTMS-diatomite). The diatomite with thermal treatment from 100 to 700°C was functionalized by MPTMS under dry and humid conditions. The obtained MPTMS-diatomite was characterized by X-ray diffraction (XRD), thermal gravity-differential scanning calorimeter (TG-DSC), and Fourier transformation infrared (FT-IR). The results showed that an increase in treatment temperature seems to reduce the loading of MPTMS onto diatomite. The humidity of diatomite was favorable for the grafting of functional groups on the surface. The possible mechanisms of MPTMS loading to diatomite (MPTMS-diatomite) were also proposed. The performance of a carbon paste electrode (CPE) modified with MPTMS-diatomite in the simultaneous determination of Cd(II) and Pb(II) ions was addressed.